2015
DOI: 10.1016/j.breast.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' interpretive efficiency and variability in true- and false-positive detection when screen-reading with tomosynthesis (3D-mammography) relative to standard mammography in population screening

Abstract: We examined interpretive efficiency and variability in true- and false-positive detection (TP, FP) for radiologists screen-reading with digital breast tomosynthesis as adjunct to full-field digital mammography (2D/3D) relative to 2D alone in population-based screening studies. A systematic literature search was performed to identify screening studies that provided radiologist-specific data for TP and FP detection. Radiologist interpretive efficiency (trade-off between TPs and FPs) was calculated using the FP:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We could speculate that the "biopsy/no biopsy" classification may have depressed specificity in our study, and that some low levels of experience among the readers may have affected confidence to state "no biopsy". It is well recognised that the sensitivity-specificity trade-off varies between readers 18 . A Swedish trial of one-view Siemens DBT versus FFDM in the primary screening context has found lower specificity alongside higher sensitivity, particularly in the early stages of the study when reader experience was lower 19 .…”
Section: Discussionmentioning
confidence: 99%
“…We could speculate that the "biopsy/no biopsy" classification may have depressed specificity in our study, and that some low levels of experience among the readers may have affected confidence to state "no biopsy". It is well recognised that the sensitivity-specificity trade-off varies between readers 18 . A Swedish trial of one-view Siemens DBT versus FFDM in the primary screening context has found lower specificity alongside higher sensitivity, particularly in the early stages of the study when reader experience was lower 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This procedure enables visualization of stones from multiple angles rather than simply anterior to posterior, and has been used extensively in breast imaging as an alternative screening modality for mammography 5456 . For patients with kidney stones, imaging at multiple angles improves sensitivity and specificity with scant increases in radiation exposure 57,58 .…”
Section: Kidney Ureter Bladder Radiographymentioning
confidence: 99%
“…One year later, Svahns et al considered the FP to TP ratios in three populationbased studies and reported improvements in radiologists' interpretive efficacy of X-ray images when a combined configuration was implemented. The results indicated 55, 48 and 30% improvement in true positive detection when a 2D-3D setup was used in lieu of traditional setup in Houston, STORM, and Oslo studies, severally [48]. In TOMMY trial in UK, 2015, increased specificity (by 9%) for all studied groups and elevated sensitivity (by 7%) for dense breasts was observed as a result of using digital and film screening [49].…”
Section: Digital Breast Tomosynthesis (Dbt)mentioning
confidence: 95%